Student Perceptions of Driverless Car Technology - Haga, Wayne; Morris, Gerry; Fustos, Janos (American Journal of Management, 2020)
The subject of driverless cars is incredibly dynamic as evidenced by the great amount of emerging literature and news items about the topic. It touches disciplines such as technology, public policy, and auto-insurance. The purpose was to explore students’ perceptions of driverless car technology. This research surveyed students using Qualtrics and was administered to both lower- and upper-level classes. Data was tabulated and broken down by attributes such as gender, age, and race. The survey results indicate the likelihood of someone buying a driverless car across these attributes. A list of both anticipated advantages and disadvantages were also tabulated.